2009
DOI: 10.1111/j.1742-4658.2009.06875.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein transport in organelles: Protein transport into and across the thylakoid membrane

Abstract: The chloroplast thylakoid is the most abundant membrane system in nature, and is responsible for the critical processes of light capture, electron transport and photophosphorylation. Most of the resident proteins are imported from the cytosol and then transported into or across the thylakoid membrane. This minireview describes the multitude of pathways used for these proteins. We discuss the huge differences in the mechanisms involved in the secretory and twin‐arginine translocase pathways used for the transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 82 publications
0
60
0
1
Order By: Relevance
“…These may integrate into the thylakoid membrane without the aid of a proteinaceous machinery, as has been shown for several single-spanning nucleus-encoded proteins (reviewed in ref. 43). On the other hand, YidC is required to integrate the AtpH ortholog in bacteria, F o c (44), and it has been suggested that many short membrane proteins with C-terminal signal anchor sequences are posttranslationally integrated by the YidC translocon (45).…”
Section: Discussionmentioning
confidence: 99%
“…These may integrate into the thylakoid membrane without the aid of a proteinaceous machinery, as has been shown for several single-spanning nucleus-encoded proteins (reviewed in ref. 43). On the other hand, YidC is required to integrate the AtpH ortholog in bacteria, F o c (44), and it has been suggested that many short membrane proteins with C-terminal signal anchor sequences are posttranslationally integrated by the YidC translocon (45).…”
Section: Discussionmentioning
confidence: 99%
“…The other examples of folded protein transport are via nuclear pores; however, no such static structure has been seen on peroxisome membranes, suggesting the translocon is assembled on demand. The other example is the tat system in chloroplasts and bacteria; again, mechanistic details are lacking, but it has been proposed that variable copies of a membrane protein tatA are recruited to form a type of annulus around the folded protein (Aldridge et al, 2009). …”
Section: Translocation and Releasementioning
confidence: 99%
“…S2). We suggest that these extremely short single-spanning membrane proteins, which integrate randomly into the thylakoid membrane in plants (30), would be difficult to transport to the thylakoid membrane if not encoded in the chloroplast genome.…”
Section: Mitochondrial Proteins Are Potential Targets For Recognitionmentioning
confidence: 99%